Carrying capacity of an urban conservation area in terms of transportation: a case study of Luang Prabang World Heritage City, in Lao PDR - Anousone Manissouk; Perera, L.A.S. Ranjith; Sajor, Edsel E.; Kunnawee Kanitpong; Asian Development Bank-Japan Scholarship Program (ADB-JSP) (Pathum Thani, Thailand : Asian Institute of Technology, 2011)
This research aims to analyze the transportation carrying capacity of the conservation area of Luang Prabang city (Lao PDR). Being a World Heritage City recognized by the UNESCO, it attracts many tourists, and also local people who depend on tourism industry, to come into the city eve1y day. The increasing number of people, goods and vehicles coming into the city can exceed the transport carrying capacity of the conservation area unless they are effectively managed. If the current tourism development trend in general and transportation trend in particular are not well understood there may be some detrimental effects on the fragile monuments and unpolluted environment. Therefore, the main intention of this study is to examine the physical carrying capacity of the conservation area for the movement of vehicles. The study finds that both preservation zone and protection zone of Luang Prabang conservation area can cope with the current flow of motorized vehicles. However, parking facilities there in may not be adequate for dealing with the situation in near future if tourism arrival and tourism service provisions expand rapidly. Therefore, the study suggests that the city should provide parking lots only for the residents and tourism services located within the conservation area, and allow only lighter and cleaner modes to transport tourists.
A thesis submitted in partial fulfillment of the requirements for the Degree of Master of Science in Urban Envirortmental Management, School of Environment Resources and Development
Thesis (M.Sc.) - Asian Institute of Technology, 2011
Keywords: Transportation -- Laos -- Luang Prabang; Luang Prabang World Heritage City